Faktor – Faktor yang Mempengaruhi Profit Distribution Management; Studi Empiris pada Bank Umum Syariah di Tiga Negara Asean Periode 2016 Q1 – 2020 Q4 - Cindy Triyas Ambarwati; Isbandini Veterina (LPMP Imperium, 2021)
This study aims to determine the effect of asset composition, deposits, effectiveness of thirdparty funds, productive asset management, and risk financing on profit distribution management of largest Islamic Banks in Indonesia, Malaysia, and Brunei Darussalam; periods 2016Q1 - 2020Q4. This study is quantitave research which use multiple regression to analyze the effects of those factors to profit distribution management. The result of this study is asset composition, deposits, and productive asset management has significantly effect on profit distribution management. But, effectiveness of thirdparty funds and risk financing don’t have effect to ptofit distributinon management. This study is modification research of Ernayani et al., 2017; Farook et al., 2012; and Mais et al., 2019.The limited availability of data causes this study couldn’t give a full picture of Asean Islamic Bank